THE PROTAGONISM IN THE STRUGGLE FOR THE QUOTA SYSTEM FOR BLACK PEOPLE IN PUBLIC UNIVERSITIES: INTERVIEW WITH ZELIA AMADOR DE DEUS: ENTREVISTA COM ZELIA AMADOR DE DEUS - Lebrego, Arina Marques (2021)
This paper reports an interview conducted with Professor Zélia Amador de Deus, on March 19th, 2022, who currently coordinates the Advisory Office of Diversity and Inclusion - ADIS, Federal University of Pará (UFPA), and who is also responsible for planning, coordination, definition, implementation and monitoring of affirmative action policies. The debate was addressed around the amendment, in 2022, of Law 12.711/2012, given its importance as a breakthrough by the Brazilian State to alleviate the effects of racism, and the political maneuvers trying to undermine the guarantee of rights already achieved. It also discussed the controversial issue of quota fraud, its impacts and ways to combat it. In the voice of Zélia Amador de Deus, we find the narrative of protagonism within the black movement, in the implementation of affirmative action policies and in favor of the quota system for black men and black women in the public universities of the Brazilian State.